Vers une communication efficace en pharmacie : une approche par contextualisation de l’interaction pharmacien-patient - Audrey Vandesrasier; Christine Thoër; Marie-Thérèse Lussier (Communiquer)
Pharmacist-patient communication is an essential element of a pharmacist’s practice, on the one hand to encourage proper use of medicines, on the other hand to help patients in their overall therapeutic success. The aim of our research is to identify the contextual elements that influence the pharmacist-patient communication and which could, according to pharmacists and patients, improve the effectiveness of pharmacist-patient communication. Our research mobilizes Street’s ecological doctor-patient interaction model where interpersonal, media, cultural, political-legal and organizational contexts are taken into account. A qualitative methodology was chosen. Semi-structured individual interviews were conducted with 7 patients and 6 pharmacists, on which a thematic content analysis was carried out. A number of elements may limit communication within the pharmacy, including the gap between the representation of both parties’ roles, the lack of privacy and the pharmacist’s time constraints. Furthermore, the boom of Internet and the evolution of the political-legal context present vastly unexplored repercussions and potential opportunities on the pharmacist-patient relationship.